2015
DOI: 10.1021/jacs.5b09682
|View full text |Cite
|
Sign up to set email alerts
|

“Smart” Ag Nanostructures for Plasmon-Enhanced Spectroscopies

Abstract: Silver is an ideal candidate for surface plasmon resonance (SPR)-based applications because of its great optical cross-section in the visible region. However, the uses of Ag in plasmon-enhanced spectroscopies have been limited due to their interference via direct contact with analytes, the poor chemical stability, and the Ag(+) release phenomenon. Herein, we report a facile chemical method to prepare shell-isolated Ag nanoparticle/tip. The as-prepared nanostructures exhibit an excellent chemical stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
142
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 47 publications
2
142
0
Order By: Relevance
“…Theeasiest way to protect aAgtip from oxidation is to store it in an itrogen glovebox with low oxygen and water content, which can prolong the lifetime of the tip to several months. [9] Thes hell-isolated tips exhibit longer lifetime;however, this chemical method is not general and tedious to scale up,g reatly limiting the application of the shell-isolated tips.T herefore,t he development of more general methods would be of great significance. [6] Thetip can also be protected by encapsulation with self-assembled monolayers (SAMs) of molecules whose Raman signals do not overlap with the signals of the analyte.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theeasiest way to protect aAgtip from oxidation is to store it in an itrogen glovebox with low oxygen and water content, which can prolong the lifetime of the tip to several months. [9] Thes hell-isolated tips exhibit longer lifetime;however, this chemical method is not general and tedious to scale up,g reatly limiting the application of the shell-isolated tips.T herefore,t he development of more general methods would be of great significance. [6] Thetip can also be protected by encapsulation with self-assembled monolayers (SAMs) of molecules whose Raman signals do not overlap with the signals of the analyte.…”
mentioning
confidence: 99%
“…[8] Recently,the Zenobi group and the Li group have developed aw et chemical method to prepare shell-isolated tips by coating silica shells onto the surface of Au or Ag tips. [9] Thes hell-isolated tips exhibit longer lifetime;however, this chemical method is not general and tedious to scale up,g reatly limiting the application of the shell-isolated tips.T herefore,t he development of more general methods would be of great significance.…”
mentioning
confidence: 99%
“…This technique is a universal approach; it has been applied in various areas, including electrochemistry, food safety, material science, and biology . We also found that the stability of Ag‐based substrates can be significantly improved using shell‐isolated nanoparticle‐enhanced Raman spectroscopy; this enhancement was preserved even after 1 month …”
Section: Introductionmentioning
confidence: 75%
“…[ 120 ] In order to meet different system requirements, different types of SHINs have been prepared. [ 126,127 ] Second, the inert shell should be very thin as the SHINERS signal intensity will be signifi cantly decreased with the increasing shell thickness. In our case, the suitable diameter of gold cores is 55 nm [ 121 ] for SHINERS measurements, and bigger diameter gold NPs, such as 120 nm, can be synthesized for enormous enhancements ( Figure 6 A,B).…”
Section: Progress Reportmentioning
confidence: 99%